Análise estrutural e modal da estrutura metálica de base de um grupo gerador diesel de 160 KVa com uso do método de elementos finitos - Marcon, Bruno (2022)
Power generation equipment’s are used in a variety of applications, from industries to agriculture, those machines are very useful on suppling power during a failure on the mains grid supply, modern installations are dependent of electric energy, those failures can cause a massive damage to business and industrial plants. Diesel generator sets are the most common machine used for this application, their simple and inexpensive construction surrounded by their highly reliable operation make them perfect for the case, despite being a non-renewable and highly polluting energy, it still proves to be the best option in those cases. The construction of these Diesel Sets is made by an Internal Combustion Diesel Engine combined with an Electric Alternator, which is responsible for generating energy, the chassis of the structure consists of a metallic base designed to allocate the parts that the machine has. This metallic base should resist to the weight of the parts and also resist to the vibrations induced by the machine.The text will present a model of a metallic structure designed for a Diesel Generator Set, then using de Finite Element Method (FEM) the tensions induced on the structure by the weight of the engine and alternator will be analyzed, at the end, again with the use of the Finite Element Method (FEM) a modal study will be developed discovering which will be the modes of vibration and in what frequencies their occur.